Electroacupuncture Alleviates Cisplatin-Induced Nausea in Rats. Issue 2 (April 2016) - Cui, Yingxue; Wang, Linpeng; Shi, Guangxia; Liu, Lu; Pei, Pei; Guo, Jianyou
Objective: Acupuncture has been shown to be effective for the treatment of chemotherapy-related nausea and vomiting. The aim of this study was to explore the mechanisms of action underlying the anti-emetic effect of electroacupuncture (EA). Design: Forty-eight rats received saline (n=12) or 6 mg/kg cisplatin (n=36) to establish a chemotherapy-induced nausea and vomiting model. EA was performed at CV12 (n=12), bilateral PC6 (n=12), or sham points (n=12) 3 days before and 1–2 days after cisplatin administration (4–5 times in total), at 0.5–1 mA intensity and 2/15 Hz frequency for 10 min. Kaolin intake, food intake and bodyweight change were evaluated as markers of nausea and vomiting severity. Concentrations of serotonin (5-hydroxytryptamine, 5-HT) in the duodenum and c-Fos expression in the nucleus of the solitary tract (NTS) were measured using high performance liquid chromatography and immunohistochemistry, respectively. Results: Cisplatin administration led to increased kaolin intake and reduced food intake and bodyweight over the following 2 days. EA at CV12 significantly reversed the cisplatin-induced change in kaolin intake (on days 1 and 2) and food intake and bodyweight (on day 1). EA at CV12 also attenuated the cisplatin-induced increase in 5-HT in the duodenum and suppressed c-Fos expression in the NTS. EA at PC6 influenced kaolin intake (on day 1 only) and c-Fos expression, but had no statistically significant effect on food intake, bodyweight or 5-HT expression. Conclusions: This study demonstrated beneficial effects of EA on chemotherapy-induced nausea and vomiting in a rat model. The anti-emetic effect of EA may be mediated through inhibition of 5-HT secretion in the duodenum and activity of the NTS.